Full-Length Transcriptome Sequencing and the Discovery of New Transcripts in the Unfertilized Eggs of Zebrafish (Danio rerio). Issue 6 (1st June 2019) - Mehjabin, Rumana; Xiong, Lv; Huang, Rong; Yang, Cheng; Chen, Geng; He, Libo; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping
Abstract: Understanding early gene expression in zebrafish embryos is a prerequisite for developmental biology research. In this study, 1, 629, 447 polymerase reads were obtained from the unfertilized eggs of zebrafish via full-length transcriptome sequencing using the PacBio RS II platform first. Then, 102, 920 unique isoforms were obtained by correction, clustering and comparison with the zebrafish genome. 12, 782 genes in the genome were captured, accounting for 39.71% of the all annotated genes. Approximately 62.27% of the 12, 782 genes have been alternatively spliced. GO and KEGG annotations revealed that the unfertilized eggs primarily stored genes that participate in RNA processing and nuclear protein complex composition. According to this PacBio data that aligned with the genome, 3, 970 fusion genes, 819 ncRNAs, and 84 new transcripts were predicted. Illumina RNA-seq and RT-qPCR detection found that the expression of two new transcripts, PB.5289.1 and PB.10209.1, were significantly up-regulated at the 2-cell stage and down-regulated rapidly thereafter, suggesting their involvement in minor ZGA during early embryonic development. This study indicated that the unfertilized eggs of zebrafish may have retained genes directly related to cell division and development to initiate the subsequent development in a limited space and time. On the other hand, NTRs or new transcriptome regions in the genome were discovered, which provided new clues regarding ZGA of MZT during early embryonic development in fish.